Pseudomonas fluorescens: Potentiality against red rot disease of sugarcane - Sharma, Geeta; Rose S., Delna (Journal of Sugarcane Research, 2021)
Red rot disease of sugarcane caused by Colletotrichum falcatum is one of the oldest known, most widespread and threatening diseases in sugarcane which should be controlled/managed as early as possible before it ruin the crop. There are multifarious strategies for red rot disease management, including chemical, physical methods and use of resistant varieties. Strains of fluorescent Pseudomonas are known to suppress the soil borne inoculum of C. falcatum surviving in the rhizosphere and to induce systemic resistance against red-rot. Especially Pseudomonas flourescens has high efficacy against red rot pathogen and enhances cane and sugar yields. Thus, it is essential to screen and evaluate bacterial strains which could be exploited for the management of red rot disease in sugarcane.